PENGARUH TEKNIK KONTRAK PERILAKU UNTUK MENGURANGI PERILAKU KECANDUAN GADGET SISWA MELALUI BIMBINGAN KELOMPOK DI SMA PGRI PEKANBARU - Tasya Sri Wulandari; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the influence of behavioral contracting techniques to reduce the gadget addiction behavior of students in SMA PGRI Pekanbaru. This type of research is a quantitative study with an experimental method using a One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was the measurement scale of gadget addiction behavior which consisted of 42 items before validation, and after validation obtained 30 items with avalid validity of 0.499 and a reliability of 0.867. The subjects of this study were 7 students who were identified as having high levels of gadget addiction behavior. The data analysis technique used was non-parametric statistical techniques using the Wilcoxon test. The results of the research proved the research hypothesis was accepted. before and after treatment is given in the form of contact behavior techniques. From the Spearman rank test results obtained correlation coefficient r = 0.817 while thedeterminant coefficient r2 is 0.667. Thus there is an influence of 66% contract behavior behavior on gadget addiction behavior.Key Words: Contract Behavior, Student Gadget Addiction Behavior,Group Conseling